Lack of Vesicular Zinc Does Not Affect the Behavioral Phenotype of Polyinosinic:Polycytidylic Acid-Induced Maternal Immune Activation Mice - Sandoval, Katy Celina; Thackray, Sarah E.; Wong, Alison; Niewinski, Nicole; Chipak, Colten; Rehal, Suhkjinder; Dyck, Richard H. (Frontiers in Behavioral Neuroscience, 2022)
Zinc is important in neural and synaptic development and neuronal transmission. Within the brain, zinc transporter 3 (ZnT3) is essential for zinc uptake into vesicles. Loss of vesicular zinc has been shown to produce neurodevelopmental disorder-like behavior, such as decreased social interaction and increased anxiety- and repetitive-like behavior. Maternal immune activation (MIA) has been identified as an environmental factor for neurodevelopmental disorders, such as autism spectrum disorders (ASDs) and schizophrenia (SZ), in offspring, which occurs during pregnancy when the mother’s immune system reacts to the exposure to viruses or infectious diseases. In this study, we investigated the interaction effect of a genetic factor (ZnT3 knockout (KO) mice) and an environmental factor (MIA). We induced MIA in pregnant female (dams) mice during mid-gestation, using polyinosinic:polycytidylic acid (polyI:C), which mimics a viral infection. Male and female ZnT3 KO and wild-type offspring were tested in five behavioral paradigms: Ultrasonic Vocalizations at postnatal day 9 (P9), Open Field Test, Marble Burying Test, 3-Chamber Social Test, and Pre-Pulse Inhibition in adulthood (P60-75). Our results indicate that loss of vesicular zinc does not result in enhanced ASD- and SZ-like phenotype compared to wild-type, nor does it show a more pronounced phenotype in male ZnT3 KO compared to female ZnT3 KO. Finally, MIA offspring demonstrated an ASD- and SZ-like phenotype only in specific behavioral tests: increased calls emitted in ultrasonic vocalizations and fewer marbles buried. Our results suggest that there is no interaction between the loss of vesicular zinc and MIA induction in the susceptibility to developing an ASD- and SZ-like phenotype.